2015
DOI: 10.1126/scitranslmed.aaa3700
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting stem cell–like memory CD8+T cells with a naïve-like profile upon yellow fever vaccination

Abstract: One Sentence Summary:The Yellow Fever vaccine induces a CD8 T stem cell-like memory subset that preserves a high degree of "Naïveness" and is stably maintained for over two decades in humans. with no studies beyond five years post-vaccination. 7Hereby, we investigated 41 vaccinees, spanning 0.27 to 35 years after vaccination. YF-8 specific CD8 T cells were readily detected in almost all donors (38/41), with frequencies 9 decreasing with time. As previously described, effector cells dominated the response early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
196
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(213 citation statements)
references
References 47 publications
16
196
0
1
Order By: Relevance
“…We studied each HBV-specific T cell response in its entirety, including naïve-like T cells 36. The median percentage of cells expressing each marker in the three infection stages is presented in figure 4 for both core 18 and pol 455 -specific T cells, with additional data on relative expression levels for select markers.…”
Section: Resultsmentioning
confidence: 99%
“…We studied each HBV-specific T cell response in its entirety, including naïve-like T cells 36. The median percentage of cells expressing each marker in the three infection stages is presented in figure 4 for both core 18 and pol 455 -specific T cells, with additional data on relative expression levels for select markers.…”
Section: Resultsmentioning
confidence: 99%
“…They further found that human Tscm mediated strong antitumor effect in mice bearing human tumors (43). In a retrospective study, Speiser and colleagues found that yellow fever vaccine-induced Tscm in human correlated to long-term protection (44). Here we show that cancer vaccine can elicit Tscm in vivo , which is associated with TCR downregulation and weak TCR signaling, and correlates with stronger antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…2). Concerning the in vivo persistence of these relatively undifferentiated memory subsets in humans the group of Daniel Speiser recently provided impressive data showing that T cells specific to yellow fever virus could be found in individuals up to 35 years after vaccination [38]. Another recent study used sequencing of specific integration sites to follow the long-term persistence of genetically modified T cell subsets after donor lymphocyte infusion [39].…”
Section: 3 Memory T Cell Ontogeny and Stemnessmentioning
confidence: 99%